Innovation and typicality in localised agri-food systems: the case of PDO Parmigiano Reggiano. Issue 12 (24th July 2019) - Mancini, Maria Cecilia; Arfini, Filippo; Guareschi, Marianna
Abstract : Purpose: The purpose of this paper is to analyse the determinants and the impact of some of the more significant innovations applied to the localised agri-food systems (LAFSs) bearing a (Geographical indication) GI product, considering the multi-faceted aspects of innovation and how the producers have managed the implementation of such innovations. Design/methodology/approach: Parmigiano Reggiano (PR) system is considered as a representative GI product, with the system showing the features of an LAFS in terms of governance, territorial reputation and quality perceived by consumers. PR innovations from 1860 to 2015 are analyszed and classified as technological and organisational. Three determinants of innovations are identified in the PR LAFS: consumer needs; value chain (VC) strategies; and governance. Finally, the innovation impact on the VC, product quality and rural development are studied. Findings: The analysis shows the positive and negative impacts of innovations. The main finding is that governance action is crucial to pursuing quality strategies and maintaining economic value at production level. Research limitations/implications: The research analyses some of the more significant innovations applied to the PR VC. Despite a large number of innovations were introduced from 1860, the authors had to choose just some of them, considering also the availability of dates. Practical implications: The research gives some recommendation to the PR Consortium, in specific, or governance institutions in LAFS context in general, to achieve rural development goals. The research shows that governance action is crucial to pursuing quality strategy and to maintaining economic value at production level. This implies that instead of simply raising yield per cow, the VC should aim at increasing (or maintaining) the value of production by the way of marketing strategies. Organisational, marketing and technological innovations adopted in synergy and in joint agreement among the chain actors would bring mutual benefit for the VC and for the territory. Social implications: The research shows the trade-off between VC competiveness and rural development. In fact, the increase of VC competiveness involves a growth of cost of production and the decrease of labour force. Thus, it creates a loss of employee and increases the distance between dairies with high amount of capital and familiar/smaller dairies which have low amount of capital to invert, that obstructs rural development especially in disadvantage area. Originality/value: The paper analyses the determinants and the impact of some of the more significant innovations applied to LAFS which are home to a GI product, considering the multi-faceted aspects of innovation and how producers have managed the implementation of such innovations. It underlines implication on territory and sustainability.